Family firms and investors' reaction to insider trades - Tan, Yew Loong (Nanyang Technological University, 2010)
The present research explores investor’s reaction to insider trades of family and non-family firms. More specifically, the study will investigate the reaction of investors toward insider trades of family and non-family firms, and whether the quality of corporate governance will influence investors’ reaction. The sample is made up of all insider trades in 2005 and 2006 of companies listed on the Singapore Exchange (SGX). A regression analysis was conducted and the results show that investors will react less positively to insider buy trades by family members when compared with insider buy trades by non-family members. In addition, investors react more positively to insider buy trades by family members when a firm implements an independent board chair structure when compared with a firm that implements a non-independent board chair structure. Implications, limitations and avenues for future research are included in this research paper.